Hubungan Kecerdasan Emosional (Aspek Kesadaran Diri) Dengan Tingkat Nyeri Pada Persalinan Kala I Di Wilayah Kerja Puskesmas Rangas Kabupaten Mamuju Sulawesi Barat - Manuntungi, Andi Ernawati (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Background: Pain during the first stage of labor is a physiological process that is very extraordinary for laboring mothers. The pain caused is difficult to accept by the mother because it is something unpleasant and painful.Objective: The purpose of this study was to determine the relationship of emotional intelligence (aspects of self-awareness) with the level of labor pain in the first stage.Methods: The research design used in conducting this research is a quantitative method with a cross sectional approach. A sample of 30 respondents was taken using accidental sampling technique. Independent variables include emotional intelligence (aspects of self-awareness), while the dependent variable is labor pain in the first stage. Data collection used the Multifactor Emotional Intelligence Scale (MEIS) questionnaire tool to measure emotional intelligence and the Numeric Rating Scale (NRS) observation sheet (0-10 scale) for labor pain. Bivariate analysis using Chi Square Test.Results: the results showed based on the Chi Square test showed a value of p=0.177> 0.05. The results of this study prove that there is no relationship between emotional intelligence (aspects of self-awareness) with the level of labor pain during the first stage at the Rangas Health Center.